The world within : [videorecording (DVD)] : C.G. Jung in his own words - Jung, C. G. (Carl Gustav), 1875-1961; Wagner, Suzanne, Ph.D; Evans, Richard I. (Richard Isadore), 1922-2015; Black, Stephen, 1912-2006; Van der Post, Laurens; Adler, Gerhard, 1904-1988; Frey-Rohn, Liliane (Kino Video, 2008)
Two programs about C.G. Jung. The first program uses Jung's writings, paintings, and footage of interviews as he tells about his work on dreams, memory, archetypal figures and the importance of ritual and fantasy. The second program features three separate interviews of Laurens van der Post, Gerhard Adler and Liliane Frey-Rohn remembering Jung.